A multi‐institutional joint study of contact dermatitis related to hair colouring and perming agents in Japan. (20th April 2017) - Ito, Akiko; Nishioka, Kazue; Kanto, Hiromi; Yagami, Akiko; Yamada, Shigeki; Sugiura, Mariko; Yasunaga, Chihiro; Yoshii, Keiko; Kobayashi, Hiromi; Adachi, Atsuko; Ikezawa, Yuko; Washizaki, Kumiko; et al.
Summary: Background: In Japan, allergic contact dermatitis caused by hair colouring agents is a considerable problem for those occupationally exposed and also for consumers. Over the last 20 years, p ‐phenylenediamine (PPD) has been a common allergen, with ∼7% positive patch test reactions. Objectives: To investigate which ingredients caused allergic contact dermatitis related to hair dye and perming solutions in Japan, to assess whether PPD is suitable for screening for hair dye allergy, and to propose allergens for a Japanese hairdresser series. Methods: We selected 19 hair cosmetic allergens, including PPD, Bandrowski's base, cysteamine HCl, and ammonium thioglycolate. Altogether 203 patients (26 males and 177 females) with suspected contact allergy to hair colouring or perming solutions at 14 hospitals in Japan were included. Results: The highest prevalence of positive reactions (35.1%) was for PPD. p‐ Methylaminophenol and o ‐aminophenol were often positive, both in the PPD‐positive and in the PPD‐negative patients. Moreover, cysteamine HCl often yielded positive test reactions. Conclusions: PPD is insufficient to diagnose contact allergy caused by to hair dyes. We recommend 13 allergens to be included in a Japanese hairdresser series.